Tissamahrama, Sri Lanka: Die Keramiksequenz und ihre Bedeutung für den frühhistorischen Fernhandel im Indischen Ozean - Schenk, Heidrun (e-Forschungsberichte des DAI, 2023)
The project comprises the final publication of the Tissamaharama pottery sequence, which represents the regional development of pottery manufactured from the 5th century BC to 12th/13th century CE in Sri Lanka. As the results yielded a scope that outreaches the island’s boundaries and provide new perspectives on pottery that came from the Roman Empire, Mesopotamia, northern India, south-east Asia and China, it distinctly illustrates cross-continental relations in the Indian Ocean region of Early Historic Period. Stratified graffiti in early Indian Brahmi script add to the research on south Asia’s history and religious formation.